Evaluation of Education Finance Policies In Improve Education Quality Original Papua In 2018 - Irwan Boinauw; Rahmawati Hussein (Universitas Muhammadiyah Tangerang, 2020)
It has been nineteen (19) years of special autonomy imposed in the land of Papua. But the problem of education in Papua and West Papua is not something new to hear. Papua and West Papua still rank 31 out of 34 provinces in Indonesia. Policies to improve the quality of human resources of Papuans are an important part of the framework for bringing prosperity to all Indonesians. This study uses a descriptive qualitative method. To see the results of the policy evaluation researchers used the theory of evaluation according to Willian N Dunn on four (4) criteria namely; Efficiency; Effectiveness; Leveling out; Responsiveness. Research Results: 1. The education budget allocation of 20% of the APBD is only 13% which has been realized, around 7% that has not been implemented. 2. Undergraduate Scholarship Program, Teacher Welfare Program, and Dropout Rate Program, which is implemented by the City Government of Sorong, has been running well. But there is no clear budget transparency from the Government related to these education financing programs. 3. Every year around 200 indigenous Papuan students are given scholarships. Teacher welfare has been noted but is not guaranteed. Weak economic students are given tuition fees. 4. The implementation of the education funding program by the City Government of Sorong is still unknown by all Sorong city residents, lack of socialization and some programs are still closed. Otonomi khusus sudah diberlakukan di tanah Papua selama sembilan belas tahun lamanya. Tetapi, masalah pendidikan di Papua dan Papua Barat bukan sesuatu yang baru untuk didengar. Papua dan Papua Barat masih menempati peringkat ke-31 dari 34 propinsi di Indonesia. Kebijakan untuk meningkatkan kualitas sumberdaya manusia Papua menjadi bagian penting dari kerangka kerja untuk membawa kesejahteraan bagi seluruh rakyat Indonesia. Penelitian ini menggunakan metode deskriptif kualitatif. Untuk melihat hasil evaluasi kebijakan, peneliti menggunakan teori evaluasi menurut Willian N Dunn pada empat (4) kriteria: Efficiency, Effectiveness, Leveling out, dan Responsiveness. Hasil Penelitian menunjukkan: pertama, alokasi anggaran pendidikan sebesar 20% dari APBD hanya 13% yang telah terealisasi, sementara sekitar 7% belum dilaksanakan. Kedua, Program Beasiswa Sarjana, Program Kesejahteraan Guru, dan Program Angka Putus Sekolah, yang dilaksanakan oleh Pemerintah Kota Sorong, sudah berjalan dengan baik meskipun tidak ada transparansi anggaran yang jelas dari pemerintah terkait program pembiayaan pendidikan. Ketiga, sekitar 200 siswa sudah mendapat beasiswa setiap tahun. Kesejahteraan guru telah dicatat meskipun tidak ada jaminan, sementara siswa dengan ekonomi lemah diberi biaya kuliah. Keempat, implementasi program pendanaan pendidikan oleh Pemerintah Kota Sorong masih belum diketahui oleh semua warga kota Sorong, terutama karena kurangnya sosialisasi dan beberapa program masih ditutup.